Micro-credentials in higher and vocational education: An innovation or a disruption? A review of the literature (Journal of Applied Learning and Teaching, 2024)
This article examines the literature on micro-credentials within the context of higher education and vocational education. It considers whether they are an innovative force for good or a disruptive force for evil.  Are they, as the literature suggests, a means of creating agency, affording equity, access, and participation in higher and vocational education for those who otherwise lacked the time, money, opportunity, or confidence to apply for further study or/and felt disenfranchised from the learning experience, or/and found the whole concept of a qualification daunting? Are they, as posited in the literature, an excellent conduit to higher and vocational education for those wishing to sample an academic or vocational subject without committing to a full degree course? Or are they, as pre-supposed in other literature, an over-simplistic alternative to the traditional academic credential, a cynical attempt to dumb down knowledge, turning higher and vocational education into a series of stackable credentials aimed at satisfying the job market, and the neoliberal thirst for more and more dollars to fund our institutions, but failing to meet the finer subtleties of the academic experience? I examine and critique the literature around this debate and argue how we might harness micro-credentials to sustain innovation and disruption positively, leveraging them to move forward within education in general and higher and vocational education in particular.